Method for manufacturing glass components that enhance metal bonding to glass substrates by creating a metal oxide layer, and glass components such as glass interposers that include a metal oxide layer
Patent Information
- Application Number
- JP2022562318
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-14
- Filing Date
- 2021-03-29
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2041-03-29
Smart Images

Figure 0007645279000007 
Figure 0007645279000008 
Figure 0007645279000009
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims priority under 35 U.S.C. §119e to U.S. Provisional Application No. 63 / 009,708, filed April 14, 2020, the contents of which are incorporated herein by reference in their entirety. [Technical field]
[0002] The present disclosure relates to methods of making glass components that enhance metallurgical bonding to glass substrates through the creation of a metal oxide layer, and glass components, such as glass interposers, that include a metal oxide layer. [Background technology]
[0003] Semiconductor packaging technology has evolved in significant ways over the years. Since the beginning, the approach to packaging increasingly complex semiconductor circuits (i.e., providing more functionality and performance in a given package) has been to increase the vertical and horizontal planar dimensions of the semiconductor chip within the package. As a practical matter, infinite expansion in the horizontal plane is not possible because the design will eventually suffer in terms of power routing and signal routing complexity, power loss issues, performance issues, manufacturing yield issues, etc.
[0004] As a result of the above, efforts have been made to scale semiconductor chips in height. These efforts include so-called planar-cubic (2.5D) integration and cubic (3D) integration, which employ interposers to interconnect two or more semiconductor chips within a single package. As used herein, the term "interposer" refers broadly to any structure that extends or completes an electrical connection between two or more electronic elements. The primary function of an interposer is to provide interconnection in such a way that two or more semiconductor chips can employ a tight terminal-to-terminal pitch, avoiding the need for via holes through each semiconductor chip itself. This technology involves flipping each semiconductor chip over its usual configuration, with the chip substrate facing up and the chip side facing down. Each chip is provided with microbump terminals (with tight pitch) that are connected to corresponding terminals on the top surface of the interposer. The opposite bottom surface of the interposer is provided with a C4 (chip-four) of neatly folded-over chip connections with suitable terminals. C Ontrolled C OLlapse C hip C The interposer is connected to the (usually organic) packaging substrate by through-substrate or C4 (connection) joints. The interposer contains a number of through-substrate vias ("through-vias") that allow electrical connections to be made from the terminals of each semiconductor chip on the top side of the interposer to the terminals of the packaging substrate on the bottom side of the interposer. Summary of the Invention [Problem to be solved by the invention]
[0005] Traditionally, the base substrate of an interposer has typically been silicon. Metallized through-vias provide pathways through the interposer for electrical signals to pass between the front and back surfaces of the interposer. Although silicon interposers are a promising and useful technology for achieving vertical integration of semiconductor chips, they have problems, particularly issues related to coefficient of thermal expansion (CTE) mismatch across the height of the stack, such as CTE butting issues between the silicon interposer and the organic packaging substrate. Undesirable CTE mismatch can result in interconnect failure between each semiconductor chip and the silicon interposer, interconnect failure between the silicon interposer and the packaging substrate, or both. In addition, silicon interposers are relatively expensive and suffer from high dielectric losses due to the semiconducting properties of silicon.
[0006] Organic interposers, such as flame retardant grade 4 (FR4), have also been introduced, but they have various problems with respect to dimensional stability.
[0007] Glass as the base substrate for interposers has solved many of the problems presented by silicon-based organic interposers. Glass is a highly advantageous substrate material for electrical signal transmission because of its dimensional stability, adjustable coefficient of thermal expansion (CTE), low electrical loss even at high frequencies, excellent thermal stability, and the ability to be molded into large panel dimensions in layers.
[0008] However, there is a problem in that metallizing through vias in glass substrates to provide conductive paths has proven difficult to date. Some conductive metals (especially copper) do not adhere well to glass, such as to both major surfaces or to the sidewalls of vias. Without being bound by theory, it is surmised that the poor bonding of conductive metals to glass is a result of the difference in the type of bond between the bond that holds the metal on one side and the bond that holds the glass on the other. In simple terms, glass is a network of covalently bonded oxide molecules (silicon dioxide, aluminum oxide, boron oxide, etc.). Metals consist of a "sea" of electrons that move freely throughout a lattice of stationary nuclei of positive ions. The bonding mechanism of glass is fundamentally different from that of metals, so there is a limit to the bonding between metal and glass. This problem can be mitigated by roughening the glass surface to which the metal is to be bonded, thereby providing a mechanical interlock between the metal and glass. However, roughening the glass surface can add other problems, making it a less than ideal approach. Therefore, a novel approach to solving the problem is required to metallize the through via holes in the glass substrate intended for use as an interposer and then bond the metal to a general glass substrate. [Means for solving the problem]
[0009] The present disclosure solves both of these problems by electrolessly plating the surface of a glass substrate in a solution containing a salt of a first metal that readily forms an oxide on its surface (covalently bonded to the oxide-rich glass substrate) and a salt of a second metal that does not readily form such an oxide (such as copper). After heat treatment, a glass component is formed in which an oxide of the first metal is covalently bonded to the surface of the glass substrate and a metal area (comprising the first metal and the second metal in metallic form) is bonded to the oxide of the first metal. Then, electroplating is performed to produce a thicker layer of the second metal (or some other metal) covering the metal area of the glass component. After another heat treatment, a glass component is formed in which an oxide of the first metal is still covalently bonded to the surface of the glass substrate and a metal area (comprising the first metal and the second metal in metallic form) is bonded to the oxide of the first metal. The first metal that readily forms an oxide on its surface acts as a bonding bridge between the oxide-rich glass substrate and the second metal that is desired to be bonded to the glass substrate. In one example, the first metal is manganese and the second metal is copper. First, a nanolayer of metal (e.g., silver) is applied to the surface of a glass substrate using a solution-based process (e.g., spin-coating) to act as a catalyst for electroless deposition of the first and second metals.
[0010] According to a first embodiment of the present disclosure, a method of manufacturing a glass component includes the steps of: (A) forming a first layer of catalytic metal on a surface of a glass substrate; (B) exposing the glass substrate having the first layer of catalytic metal to a temperature of 150° C. to 600° C. for at least 2 minutes; (C) forming a second layer of an alloy of a first metal and a second metal on the first layer; and (D) exposing the glass substrate having the second layer of an alloy of the first metal and the second metal on the first layer of catalytic metal to a temperature of 250° C. to 600° C. for at least 30 minutes to form a glass component, the glass component comprising: (i) a glass substrate; (ii) an oxide of a first metal covalently bonded to the glass substrate; and (iii) a metal region bonded to the oxide of the first metal, the metal region including the catalytic metal in elemental form, the first metal in elemental form, and the second metal in elemental form.
[0011] According to a second embodiment of the present disclosure, the method of the first embodiment further includes forming a third layer of a primary metal on the metal region of the glass component.
[0012] According to a third embodiment of the present disclosure, the method of the first embodiment further includes exposing the glass component having the third layer of the primary metal to a temperature of 250° C. to 600° C. in an inert environment for at least 30 minutes to form a glass component comprised of (i) the glass substrate, (ii) an oxide of the first metal covalently bonded to the glass substrate, and (iii) a new metal region comprising the catalytic metal, the first metal in elemental form, the second metal in elemental form, and the primary metal in elemental form.
[0013] According to a fourth embodiment of the present disclosure, in any one of the first to third embodiments, the catalytic metal includes one or more of silver, gold, cobalt, cobalt-phosphorus alloy, nickel or nickel-phosphorus alloy, palladium, and platinum.
[0014] According to a fifth embodiment of the present disclosure, in any one of the first to fourth embodiments, the step of forming a first layer of catalytic metal on a surface includes the steps of contacting the surface with a suspension in which nanoparticles of the catalytic metal are dispersed in a liquid support, and evaporating the liquid support.
[0015] According to a sixth embodiment of the present disclosure, in the fifth embodiment, contacting the surface with the suspension includes spinning the suspension onto the surface.
[0016] According to the seventh embodiment of the present disclosure, in any one of the first to sixth embodiments, the glass substrate has a first surface and a second surface as its two main surfaces, and sidewall surfaces defining a through via hole that opens at the first surface and the second surface and extends through the glass substrate, and an oxide of a first metal is covalently bonded to the sidewall surfaces of the through via hole.
[0017] According to an eighth embodiment of the present disclosure, in the third embodiment, the glass substrate has a first surface and a second surface as its two main surfaces, and sidewall surfaces defining a through via hole that opens at the first surface and the second surface and extends through the glass substrate, an oxide of a first metal is covalently bonded to the sidewall surface of the through via hole, and a new metal region forms a conductive path through the through via hole.
[0018] According to a ninth embodiment of the present disclosure, in any one of the first to sixth embodiments, the glass substrate has a first surface and a second surface as its two main surfaces, and a sidewall surface defining a blind via hole that opens on one of the first surface and the second surface and extends insufficiently through the glass substrate, and an oxide of a first metal is covalently bonded to the sidewall surface of the blind via hole.
[0019] According to a tenth embodiment of the present disclosure, in any one of the first to ninth embodiments, the first metal of the second layer includes one or more of tantalum, niobium, aluminum, manganese, rhenium, hafnium, chromium, zirconium, titanium, indium, tungsten, magnesium, molybdenum, nickel, and zinc, and the second metal of the second layer includes one or more of silver, palladium, and copper.
[0020] According to an eleventh embodiment of the present disclosure, in any one of the first to tenth embodiments, the oxide of the first metal excludes a second metal.
[0021] According to a twelfth embodiment of the present disclosure, in any one of the first to tenth embodiments, the second metal of the second layer is copper.
[0022] According to a thirteenth embodiment of the present disclosure, in any one of the first to twelfth embodiments, the first metal of the second layer is manganese or zinc.
[0023] According to a fourteenth embodiment of the present disclosure, in any one of the first to thirteenth embodiments, the oxide of the first metal of the alloy has an absolute value of the enthalpy of formation greater than 600 kJ per mole, and the oxide of the second metal of the alloy has an absolute value of the enthalpy of formation less than 600 kJ per mole.
[0024] According to a fifteenth embodiment of the present disclosure, in any one of the first to fourteenth embodiments, the step of forming the second layer of alloy includes a step of producing the second layer on the first layer by electroless plating using a solution having a salt of the first metal dissolved therein and a salt of the second metal dissolved therein.
[0025] According to a sixteenth embodiment of the present disclosure, in the fifteenth embodiment, the solution further comprises formaldehyde and has a pH greater than 11.
[0026] According to the seventeenth embodiment of the present disclosure, in the fifteenth embodiment, the solution further comprises dimethylamine borane and has a pH of 6 to 8.
[0027] According to an 18th embodiment of the present disclosure, in any one of the 1st to 17th embodiments, the step of exposing the glass substrate having a first layer of catalytic metal thereon and a second layer of an alloy of a first metal and a second metal to a temperature of 250°C to 600°C includes increasing the temperature at a rate of 1°C per minute or slower.
[0028] According to a nineteenth embodiment of the present disclosure, in any one of the first to eighteenth embodiments, the step of exposing the glass substrate having the first layer of catalytic metal and the second layer of alloy of the first metal and the second metal thereon to a temperature of 250°C to 600°C is carried out with the glass substrate in the presence of air, and the method further comprises exposing the glass component to a temperature of 225°C to 275°C for at least 30 minutes with the glass component in the presence of forming gas after exposing the glass component to a temperature of 375°C to 425°C.
[0029] According to the twentieth embodiment of the present disclosure, in the second embodiment, the primary metal includes one or more of silver, gold, cadmium, chromium, copper, nickel, lead, platinum, and tin.
[0030] According to a twenty-first embodiment of the present disclosure, in a second embodiment, the primary metal comprises copper.
[0031] According to a twenty-second embodiment of the present disclosure, in any one of the second, twentieth, and twenty-first embodiments, the third layer has a thickness of 2 μm to 5 μm.
[0032] According to a 23rd embodiment of the present disclosure, in any one of the 2nd embodiment and the 20th embodiment to the 22nd embodiment, the step of forming a third layer of a primary metal on the metal region of the glass component includes a step of producing the third layer of a primary metal on the metal region of the glass component by electroplating.
[0033] According to a twenty-fourth embodiment of the present disclosure, in the twenty-third embodiment, the electroplating step utilizes a plating solution including copper sulfate.
[0034] According to a 25th embodiment of the present disclosure, in any one of the first to twenty-fourth embodiments, the step of exposing the glass substrate having the first layer of catalytic metal to a temperature of 150°C to 600°C for at least 2 minutes includes exposing the glass substrate having the first layer of catalytic metal to a temperature of 325°C to 375°C for at least 2 minutes, and the step of exposing the glass substrate having the second layer of an alloy of a first metal and a second metal provided on the first layer of catalytic metal to a temperature of 250°C to 600°C for at least 30 minutes includes exposing the glass substrate having the second layer of an alloy of a first metal and a second metal provided on the first layer of catalytic metal to a temperature of 300°C to 425°C for at least 30 minutes.
[0035] According to a 26th embodiment of the present disclosure, in the third embodiment, the step of exposing the glass substrate provided with the first layer of catalytic metal to a temperature of 150°C to 600°C for at least 2 minutes includes exposing the glass substrate provided with the first layer of catalytic metal to a temperature of 325°C to 375°C for at least 2 minutes, the step of exposing the glass substrate provided with the second layer of alloy of the first metal and the second metal on the first layer of catalytic metal to a temperature of 250°C to 600°C for at least 30 minutes includes exposing the glass substrate provided with the second layer of alloy of the first metal and the second metal on the first layer of catalytic metal to a temperature of 300°C to 425°C for at least 30 minutes, and the step of exposing the glass component provided with the third layer of primary metal to a temperature of 250°C to 600°C in an inert environment for at least 30 minutes includes exposing the glass component provided with the third layer of primary metal to a temperature of 300°C to 400°C in an inert environment for at least 30 minutes.
[0036] According to a twenty-seventh embodiment of the present disclosure, in the third embodiment or the twenty-sixth embodiment, the inert environment is a reduced pressure environment.
[0037] According to a 28th embodiment of the present disclosure, a glass interposer is a glass substrate having a first surface and a second surface as two main surfaces on the front and rear sides, and a through via hole extending through its thickness from the first surface to the second surface, the through via hole comprising the glass substrate having sidewall surfaces and a central axis, a metal region disposed around the central axis inside the through via hole, and an oxide of a first metal covalently bonded to the sidewall surface of the through via hole, the oxide of the first metal being disposed between the sidewall surface and the metal region, and the metal region including the first metal in elemental form and the second metal in elemental form.
[0038] According to a twenty-ninth embodiment of the present disclosure, in a twenty-eighth aspect, the first metal is one or more of tantalum, niobium, aluminum, manganese, rhenium, hafnium, chromium, zirconium, titanium, indium, tungsten, magnesium, molybdenum, nickel, and zinc, and the second metal is one or more of silver, palladium, and copper.
[0039] According to the 30th embodiment of the present disclosure, in the 28th embodiment, the oxide of the first metal has an absolute value of the enthalpy of formation greater than 325 kJ per mole, and the oxide of the second metal has an absolute value of the enthalpy of formation less than 175 kJ per mole.
[0040] According to the thirty-first embodiment of the present disclosure, in the twenty-eighth embodiment, the first metal is manganese and the second metal is copper.
[0041] According to a thirty-second embodiment of the present disclosure, in any one of the twenty-eight to thirty-first embodiments, the metal region further comprises silver.
[0042] Various other features and advantages are set forth in the detailed description below, some of which will be readily apparent to those skilled in the art from the detailed description, and some of which will be readily discernible to those skilled in the art by practicing the embodiments as described in the detailed description below and in the appended claims.
[0043] Both the foregoing summary and the following detailed description are exemplary only and are intended to provide an overview or framework for understanding the nature and character of the claims. [Brief description of the drawings]
[0044] [Figure 1] 1 is a perspective view illustrating a glass substrate for use as an interposer, in which a via hole extends through the thickness of the glass substrate from a first surface to a second surface. [Diagram 2] FIG. 2 is an elevational cross-sectional view taken along line II-II of FIG. 1 illustrating the glass substrate of FIG. 1, in which the via holes each have a central axis perpendicular to the first and second surfaces and have sidewall surfaces defining the hole. [Diagram 3] FIG. 2 is a flow diagram illustrating various steps for forming multiple metal layers and heat treating the metal layers in a method for manufacturing a glass component, such as an interposer. [Figure 4] 4 is an elevational cross-sectional view taken along line IV-IV in FIG. 1 , illustrating the glass substrate of FIG. 1 after a step in the method of FIG. 3 , in which a first layer of catalytic metal is formed on the sidewall surface of the via hole. [Diagram 5] 5 is a cross-sectional elevation view similar to FIG. 4 but illustrating the formation of a second layer of an alloy of a first metal and a second metal on the first layer of catalytic metal after the remaining steps of the method of FIG. 3. [Figure 6] FIG. 6 is an elevational cross-sectional view similar to FIG. 5, but illustrating another step of the method of FIG. 3, in which an oxide of a first metal is formed from a second layer bonded to a sidewall surface of the glass substrate, and further illustrating that a metal region containing the first metal, the second metal, and a catalytic metal, all in elemental form, is disposed over the oxide of the first metal. [Figure 7] FIG. 7 is an elevational cross-sectional view similar to FIG. 6, but illustrating a further step in the method of FIG. 3, in which a third layer of the primary metal is deposited over the metal area to fill the remaining gaps in the via hole, thus fully metallizing the via hole. [Figure 8] FIG. 8 is an elevational cross-sectional view similar to FIG. 7, but illustrating a new metal region after yet another step of the method of FIG. 3, in which an oxide of the first metal is disposed between and bonded to the sidewall surface and the new metal region, the new metal region including the first metal, the second metal, the catalytic metal, and the primary metal, all in elemental form. [Figure 9] Photograph showing tape pull test results for sample glass parts made according to the method of FIG. 3, illustrating that the tape did not significantly peel the fresh metal areas off the first side of the glass substrate, thus demonstrating a high level of adhesion. [Figure 10] Photograph of tape pull test results for another sample glass part made according to the method of FIG. 3 illustrating that the tape did not significantly peel the fresh metal areas from the first side of the glass substrate, thus demonstrating a high level of adhesion. [Figure 11]Photograph of tape pull test results for another sample glass part made according to the method of FIG. 3 illustrating that the tape did not significantly peel the fresh metal areas off the first side of the glass substrate, thus demonstrating a high level of adhesion. [Figure 12] Photograph showing the results of a tape pull test on a sample glass part not made according to the method of FIG. 3, illustrating that the tape pulled much of the deposited metal off the first side of the glass substrate, thus indicating a low level of adhesion. [Figure 13] Photograph showing the results of a tape pull test on another sample glass part not made according to the method of FIG. 3, illustrating that the tape pulled much of the deposited metal off the first side of the glass substrate, thus indicating a low level of adhesion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0045] Reference will now be made in detail to the preferred embodiments of the present invention, various examples of which are illustrated in the accompanying drawings. Wherever possible, the same reference numbers are used throughout the drawings to refer to the same or like parts.
[0046] Glass Substrate 1 and 2, a glass substrate 100 is illustrated in the form of an interposer. The glass substrate 100 has a first surface 102 and a second surface 104. In embodiments, the first surface 102 and the second surface 104 are the two major surfaces of the glass substrate 100, and are at least approximately parallel and generally oriented in opposite directions.
[0047] In various embodiments, the glass substrate 100 is an alkaline earth aluminoborosilicate glass substrate, an alkali aluminoborosilicate glass substrate, an alkali aluminoborosilicate glass substrate, or fused silica (including high purity fused silica). In other embodiments, the glass substrate 100 is free of alkali components, such as an alkali-free aluminoborosilicate glass substrate or an alkali-free aluminoborosilicate glass substrate. By "alkali-free" it is meant that there is no alkali metal in the glass substrate 100 in any intended amount, and any alkali metal in the glass substrate 100 is present as an impurity. In various embodiments, the composition of the glass substrate 100 includes the following (in mole percent on an oxide basis): 60 mol % to 78 mol % SiO2, 6 mol % to 15 mol % Al2O3.
[0048] For example, in some embodiments, the glass substrate 100 may include the following (mol percentages on an oxide basis): 64.0 mol% to 71.0 mol% SiO2, 9.0 mol% to 12.0 mol% Al2O3, 7.0 mol% to 12.0 mol% B2O3, 1.0 mol% to 3.0 mol% MgO, 6.0 mol% to 11.5 mol% CaO, 0 mol% to 2.0 mol% SrO, 0 mol% to 0.1 mol% BaO, and at least 0.01 mol% SnO2, where 1.00≦Σ[RO] / [Al2O3]≦1.25, where [Al2O3] is the mole percentage of Al2O3 and Σ[RO] is equal to the sum of the mole percentages of MgO, CaO, SrO, and BaO. In each such embodiment, the glass substrate 100 has a coefficient of thermal expansion (CTE) of 20×10 at room temperature. -7 / ℃ or 50×10 -7 / °C, e.g., 28 x 10 -7 / ℃ or 34×10 -7 / °C, and for example, 31.7 x 10 -7 / °C. Terms such as "CTE" and "coefficient of thermal expansion" refer to how the dimensions of an object change with a change in temperature. The coefficient of thermal expansion (CTE) is a measure of the fractional change in dimension per degree Celsius change in temperature at constant pressure, but this dimension could refer to, for example, volume, area, or linear dimension.
[0049] In some embodiments, the glass substrate 100 includes the following (mol percentages on an oxide basis): 61 mol % to 75 mol % SiO2, 7 mol % to 15 mol % Al2O3, 0 mol % to 12 mol % B2O3, 9 mol % to 21 mol % Na2O, 0 mol % to 4 mol % K2O, 0 mol % to 7 mol % MgO, and 0 mol % to 3 mol % CaO.
[0050] In some embodiments, the glass substrate 100 may include the following (by mole percentage on an oxide basis): 60 mol % to 70 mol % SiO2, 6 mol % to 14 mol % Al2O3, 0 mol % to 15 mol % B2O3, 0 mol % to 15 mol % Li2O, 0 mol % to 20 mol % Na2O, 0 mol % to 10 mol % K2O, 0 mol % to 8 mol % MgO, It contains 0 mol% to 10 mol% CaO, 0 mol% to 5 mol% ZrO2, 0 mol% to 1 mol% SnO2, 0 mol% to 1 mol% CeO2, less than 50 ppm (50 mg / L) As2O3, and less than 50 ppm (50 mg / L) Sb2O3, where 12 mol%≦Li2O+Na2O+K2O≦20 mol% and 0 mol%≦MgO+CaO≦10 mol%.
[0051] In some embodiments, the glass substrate 100 may contain the following (by mole percentage on an oxide basis): 64 mol% to 68 mol% SiO2, 12 mol% to 16 mol% Na2O, 8 mol% to 12 mol% Al2O3, 0 mol% to 3 mol% B2O3, 2 mol% to 5 mol% K2O, 4 mol% to 6 mol% MgO, and 0 mol% to 5 mol% CaO. In this case, 66 mol%≦SiO2+B2O3+CaO≦69 mol%, Na2O+K2O+B2O3+MgO+CaO+SrO>10 mol%, 5 mol%≦MgO+CaO+SrO≦8 mol%, (Na2O+B2O3)-Al2O3≦2 mol%, 2 mol%≦Na2O-Al2O3≦6 mol%, and 4 mol%≦(Na2O+K2O)-Al2O3≦10 mol%.
[0052] In some embodiments, the glass substrate 100 may include the following (mol percentages on an oxide basis): 66 mol% to 78 mol% SiO2, 4 mol% to 11 mol% Al2O3, 4 mol% to 11 mol% B2O3, 0 mol% to 2 mol% Li2O, 4 mol% to 12 mol% Na2O, 0 mol% to 2 mol% K2O, 0 mol% to 2 mol% ZnO, 0 mol% to 5 mol% MgO, 0 mol% to 2 mol% CaO, 0 mol% to 5 mol% SrO, 0 mol% to 2 mol% BaO, and 0 mol% to 2 mol% SnO2.
[0053] In some embodiments, the glass substrate 100 contains (mol percentages on an oxide basis): 69.49 mol % SiO2, 8.45 mol % Al2O3, 14.01 mol % Na2O, 1.16 mol % K2O, 0.185 mol % SnO2, 0.507 mol % CaO, 6.2 mol % MgO, 0.01 mol % ZrO2, and 0.008 mol % Fe2O3.
[0054] In various embodiments, the glass substrate 100 is made by a glass manufacturing system that utilizes a melting process to create glass sheets that are then cut into the desired shape of the glass substrate 100. The melting process forms the glass substrate 100 with a uniform thickness already, e.g., a total thickness variation (TTV) of less than 1.0 μm. Thus, polishing or other finishing steps may not be required before the glass substrate 100 can be used as an interposer. If the glass sheet resulting from the melting process would result in the thickness 106 of the glass substrate 100 being thicker than desired, the thickness 106 of the glass substrate 100 can be reduced by any known means, such as etching or polishing. In still other embodiments, the glass substrate 100 is made by a non-melting process and then polished or etched to have the desired thickness 106. After the glass substrate 100 is made, it may be annealed to reduce residual stresses present therein.
[0055] The thickness 106 of the glass substrate 100, in the illustrated embodiment, extends from both the first surface 102 and the second surface 104. In various embodiments, the thickness 106 is in the range of 25 μm to about 1 mm, although smaller and larger thicknesses 106 are contemplated. For example, for various embodiments described herein, the thickness 106 of the glass substrate 100 is about 50 μm, about 100 μm, about 200 μm, about 300 μm, about 400 μm, about 500 μm, about 600 μm, about 700 μm, about 800 μm, about 900 μm, about 1 mm, or any range inclusive therein, such as, for example, 50 μm to 300 μm. In various embodiments, the thickness 106 is in the range of 50 μm to 100 μm. The glass substrate 100 may have any desired shape. In various embodiments, the glass substrate 100 has a circular shape. In these embodiments, the glass substrate 100 may range in diameter from 200 mm to 300 mm. In other embodiments, the glass substrate 100 has a square or rectangular shape.
[0056] The glass substrate 100 further includes one or more via holes 108. In each embodiment, the glass substrate 100 includes a plurality of via holes 108. In each embodiment, a portion or all of the one or more via holes 108 extend from the first surface 102 to the second surface 104 through the thickness 106 of the glass substrate 100. Such a via hole 108 may be referred to herein as a "through via hole." The through via hole 108 is open at the first surface 102 and the second surface 104. In other embodiments, a portion or all of the one or more via holes 108 may only partially extend through the thickness 106 even if they are open to the first surface 102, and do not extend to the second surface 104 over the entire length of the thickness 106. Such a via hole 108 may be referred to herein as a "blind via hole." In each embodiment, the glass substrate 100 includes a plurality of both through via holes 108 and blind via holes 108. Sidewall surfaces 110 define each of the via holes 108 within the thickness 106 of the glass substrate 100 .
[0057] The via holes 108 are labeled with a diameter 112. Although the diameter 112 of each of the via holes 108 appears to be the same size, this is not necessarily the case, i.e., the diameter 112 of each of the via holes 108 may vary within the same glass substrate 100. In various embodiments, the diameter 112 is in the range of five microns (5 μm) to one hundred fifty microns (150 μm). In some embodiments, such as the illustrated embodiment, the via holes 108 have an hourglass shape with a waist 114 where the diameter 112 of the via holes 108 is narrower near the first side 102 of the glass substrate 100, narrower near the second side 104, or narrower near both sides. The hourglass shape aids in better electroplating, as described further below. In other embodiments, the via holes 108 have a generally cylindrical or generally conical shape.
[0058] Each of the via holes 108 has a central axis 116. The central axis 116 of one via hole 108 is separated from the central axis 116 of an adjacent via hole 108 by a pitch (distance) of 118. The pitch 118 can be any value depending on the desired application, such as, but not limited to, between about 10 μm and about 2000 μm, such as about 10 μm, about 25 μm, about 50 μm, about 100 μm, about 250 μm, about 500 μm, about 1000 μm, about 2000 μm, or any other value or range between any two of the preceding values (including both upper and lower limits). For example, the pitch 118 can be in the range of 10 μm to 100 μm, the range of 25 μm to 500 μm, the range of 10 μm to 1000 μm, or the range of 250 μm to 2000 μm. The pitch 118 of the same glass substrate 100 may vary or may be constant. The pitch 118 may be set, for example, to have between 1 and 20 via holes 108 per square millimeter, depending on the interposer design and application. In some embodiments, the via holes 108 are patterned throughout the glass substrate 100. In other embodiments, the via holes 108 do not form any pattern.
[0059] The via hole 108 is formed in the glass substrate 100 using one of a variety of forming techniques. For example, the via hole 108 can be formed by various mechanical drilling, etching, laser ablation, laser assisted machining, laser damage followed by etching, abrasive blasting, abrasive water jet machining, focused electron thermal energy, or any other suitable forming technique. In the laser damage followed by etching process, a laser is used to initially form a damage mark in the glass substrate 100, which is then modified along the damage mark. An etching solution is then applied to the glass substrate 100. The glass substrate 100 is thinned by the etching solution. Since the etching rate of the glass substrate 100 is faster near the damage mark, the damage mark is preferentially etched so that the via hole 108 is opened through the glass substrate 100.
[0060] A method 200 for metallizing a glass substrate 100, such as by metallizing a via hole 108. 3-6, the via holes 108 in the glass substrate 100 are metallized according to a novel method, designated 200, described herein. Although the method 200 is described in the context of metallizing the via holes 108 in addition to using the glass substrate 100 as an interposer, the method 200 may be intended to place metal on the glass substrate 100 for any purpose, and the metallization of each surface should be interpreted to refer to surfaces other than the sidewall surface 110 of the via hole 108, such as the first surface 102, the second surface 104, the surfaces of other perforations through the glass substrate 100, or various combinations thereof. As noted in the Background of the Invention, in the context of using the glass substrate 100 as an interposer, metallizing the via holes 108 provides a conductive path through the interposer for electrical signals to pass from the first surface 102 to the second surface 104.
[0061] Forming a First Layer of Catalytic Metal 120: In step 202, the method 200 includes forming a first layer of catalytic metal 120 on a surface of the glass substrate 100 (see, in particular, FIG. 4). In various embodiments, the first layer of catalytic metal 120 may cover all or substantially all of the glass substrate 100. In various embodiments, such as the illustrated embodiment, step 202 includes forming the first layer of catalytic metal 120 on a sidewall surface 110 of a via hole 108 in the glass substrate 100. In other embodiments, step 202 includes forming the first layer of catalytic metal 120 on the first surface 102 or the second surface 104, or on both the first surface 102 and the second surface 104. Alternatively, the first layer of catalytic metal 120 may be patterned to cover a portion of the glass substrate 100 on a portion of the first surface 102, a portion of the second surface 104, a portion or all of the sidewall surface 110 of the via hole 108, or any combination of the aforementioned surfaces. The patterning may be performed by selectively masking certain areas of the glass substrate 100 with a barrier tape, photoresist, or the like, during deposition of the first layer of catalytic metal 120 onto the glass substrate 100.
[0062] The catalytic metal is catalytic in the sense that it facilitates the deposition of a subsequent metal layer thereover, by electroless deposition or other methods. In embodiments, the catalytic metal comprises one or more of silver, gold, cobalt, cobalt-phosphorus alloy, nickel, nickel-phosphorus alloy, palladium, and platinum. In embodiments, the catalytic metal is or comprises essentially silver or palladium. In embodiments, the first layer of catalytic metal 120 is a nanolayer having a thickness, designated 122, in the range of 5 nm to 10,000 nm, for example, in the range of 5 nm to about 100 nm.
[0063] In each embodiment, the first layer of catalytic metal 120 is or essentially contains silver, and step 202 of method 200 includes forming the first layer of catalytic metal silver 120 on the sidewall surface 110 of the via hole 108 of the glass substrate 100.
[0064] In each embodiment, forming a first layer 120 of catalytic metal on the sidewall surface 110 of the via hole 108 of the glass substrate 100 (or any other desired surface of the glass substrate 100) includes (i) contacting the sidewall surface 110 of the glass substrate 100 with a suspension of catalytic metal nanoparticles dispersed in a liquid carrier, and (ii) evaporating the liquid carrier. The liquid carrier may be water or a solvent-based liquid. The solvent-based liquid carrier may be a single solvent, a mixture of solvents, or a solvent (single solvent or mixture of solvents) containing multiple non-solvent components. Specific solvents that may be utilized include, but are not limited to, hydrocarbons, halogenated hydrocarbons, alcohols, ethers, ketones, and the like, or various mixtures of the foregoing, such as, for example, 2-propanol (also known as isopropanol, IPA, or isopropyl alcohol), tetrahydrofuran (THF), ethanol, chloroform, acetone, butanol, octanol, pentane, hexane, heptane, cyclohexane, and various mixtures thereof. An example suspension contains catalytic metal nanoparticles in cyclohexane at a concentration of 10% W / V to 30% W / V. Evaporation of the liquid carrier leaves catalytic metal nanoparticles on the sidewall surface 110 of the via hole 108 of the glass substrate 100.
[0065] The term "nanoparticle" refers to particles or components having an average diameter (or cross-sectional dimension) along their shortest axis of about 1 nm to about 10,000 nm. It should be understood that the particle size of a nanoparticle may be a distribution characteristic. Moreover, in some embodiments, nanoparticles may have multiple sizes or distributions, or may have more than one size or distribution. Thus, a particular size may refer to an average particle size that is associated with a distribution of individual particle sizes. In some embodiments, the nanoparticles have an average diameter of about 5 nm to about 10,000 nm, about 5 nm to about 7,500 nm, about 5 nm to about 5,000 nm, about 5 nm to about 2,500 nm, about 5 nm to about 2,000 nm, about 5 nm to about 1,500, about 5 nm to about 1,250 nm, about 5 nm to about 1,000 nm, about 5 nm to about 750 nm, about 5 nm to about 500 nm, about 5 nm to about 250 nm, about 5 nm to about 200 nm, about 5 nm to about 150 nm, about 5 nm to about 125 nm, about 5 nm to about 100 nm, about 5 nm to about 7 Such as 5 nm, about 5 nm to about 50 nm, about 5 nm to about 25 nm, about 5 nm to about 20 nm, and about 5 nm to about 15 nm, such as about 5 nm, 10 nm, 20 nm, 25 nm, 50 nm, 75 nm, 100 nm, 125 nm, 150 nm, 175 nm, 200 nm, 250 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, 1250 nm, 1500 nm, 2000 nm, 2500 nm, 5000 nm, 7500 nm, or 10000 nm. The size of the nanoparticles can be measured by a variety of methods, such as dynamic light scattering techniques or by using a transmission electron microscope (TEM). For example, as is understood in the art, particle size distributions are often determined by transmission electron microscope image analysis of samples consisting of hundreds of different nanoparticles.
[0066] Nanoparticles may have any shape or surface characteristics. Nanoparticles may have a variety of structures and surface shapes, and the present disclosure is not intended to be limited to any particular surface shape, structure, or both. Although embodiments herein feature a plurality of nanoparticles, individual nanoparticles or groups of individual nanoparticles may have the same structure or surface shape as other nanoparticles, or may have different structures or surface shapes. For example, in some embodiments, nanoparticles may have spherical, ellipsoidal, polyhedral, flaky, or crystalline structures. In some embodiments, nanoparticle surfaces may be smooth, rough, regular, irregular, patterned, or the like.
[0067] In various embodiments, the metal nanoparticles are silver nanoparticles, in some embodiments having an average diameter of 10 nm to 13 nm and dispersed in cyclohexane at a concentration of 20% w / v (commercially available from CeriOn, LLC, Rochester, NY, USA).
[0068] Prior to contacting the glass substrate 100 with the nanoparticle suspension, the nanoparticle suspension may optionally be sonicated to aid in dispersing the nanoparticles throughout the liquid carrier. For example, the nanoparticle suspension may be sonicated for a period of time ranging from 15 minutes to 45 minutes, e.g., about 30 minutes.
[0069] As discussed above, the first layer 120 of catalytic metal is a nanolayer having a thickness in the range of 5 nm to 10,000 nm, for example, in the range of 5 nm to about 100 nm. The first layer 120 may be comprised of a sub-monolayer, monolayer, or multiple monolayers of nanoparticles. In various embodiments, the first layer 120 of catalytic metal is not uniform, but rather is a single type of particle or a multi-particle cluster on the sidewall surface 110 (or on the first surface 102 or second surface 104, as the case may be) of the via hole 108 of the glass substrate 100, with a majority of the sidewall surface 110 remaining bare.
[0070] In each embodiment, contacting the desired surface of the glass substrate 100 (e.g., the first surface 102, the second surface 104, the sidewall surface 110, etc.) with the suspension of catalytic metal nanoparticles includes spinning the surface of the glass substrate 100 at any speed and for any time deemed suitable to form a desired nanoparticle layer of nanoparticle-like metal catalyst on the glass substrate 100. For example, the suspension of nanoparticles may be deposited on the glass substrate 100 while spinning at a speed of 1000 rpm to 5000 rpm (e.g., 1000 rpm, 2000 rpm, 3000 rpm, 4000 rpm, or 5000 rpm, etc.) for about 30 seconds, less than 30 seconds, or more than 30 seconds.
[0071] In each embodiment, contacting the desired surface of the glass substrate 100 (e.g., first surface 102, second surface 104, sidewall surface 110, etc.) with the suspension of catalytic metal nanoparticles includes dip coating the desired surface of the glass substrate 100 in the suspension of nanoparticles or spray coating the suspension of nanoparticles onto the surface of the glass substrate 100. The dip coating may be performed at any withdrawal speed (sometimes referred to as a pull-out speed) suitable for forming the first layer 120 of catalytic metal on the surface of the glass substrate 100, such as 30 mm per minute to 35 mm per minute.
[0072] The above-described solution-based processes for forming the first layer 120 of catalytic metal on the surfaces (e.g., first surface 102, second surface 104, sidewall surface 110, etc.) of the glass substrate 100 are an improvement over non-solution-based processes such as vacuum deposition. The above-described solution-based processes, such as spin-on and dip coating, are less expensive than vacuum deposition. In addition, while such solution-based processes can form the first layer 120 of catalytic metal on the sidewall surface 110 of the via hole 108, vacuum deposition reduces the likelihood of completely covering the sidewall surface 110 of the via hole 108 with the first layer 120 as the aspect ratio of the via hole 108 increases.
[0073] Heat treating the glass substrate 100 with the first layer 120 of catalytic metal: In step 204, the method 200 further includes exposing the glass substrate 100 with the first layer 120 of catalytic metal to a temperature of 150° C. to 600° C. for at least 2 minutes. In various embodiments, the temperature ranges from 250° C. to 400° C., such as about 325° C. to about 375° C., such as about or exactly 350° C. In various embodiments, the duration is 2 minutes to 5 minutes. Step 204 may be referred to herein as “heat treating” the glass substrate 100 with the first layer 120 of catalytic metal deposited thereon. If the first layer 120 of catalytic metal is susceptible to oxidation, step 204 may be performed in an inert atmosphere (e.g., nitrogen gas atmosphere), otherwise a subsequent heat treatment in a reducing atmosphere (e.g., hydrogen gas atmosphere) may be performed to reduce the oxidized catalytic metal back to elemental form. The oxidized first layer 120 of catalytic metal can prevent the application of a second layer of metal later in method 200 (discussed below). In embodiments where the first layer 120 of catalytic metal is silver, the silver does not oxidize in the presence of air during the heat treatment step 204 of method 200. In embodiments, the glass substrate 100 is exposed to room temperature and then subjected to a temperature ramp rate (e.g., a ramp rate between 0.5° C. per minute and 10° C. per minute). In other embodiments, the glass substrate 100 with the first layer 120 of catalytic metal is placed directly into a preheated furnace set to a predetermined temperature within the operable range of step 204. Step 204 can be performed by placing the glass substrate 100 with the first layer 120 of catalytic metal in a vertical furnace, a tube furnace, or a rapid thermal ablation apparatus (RTA), or by placing it on a hot plate, etc. In embodiments utilizing palladium as the catalytic metal in first layer 120, step 204 may be omitted, that is, method 200 may not include step 204.
[0074] Forming a second layer 124 of alloy on the first layer 120: In step 206, the method 200 further includes forming a second layer 124 of an alloy of the first metal and the second metal on the first layer 120. In embodiments in which the first layer 120 is not uniform and a large portion of the sidewall surface 110 remains exposed, the second layer 124 of an alloy of the first metal and the second metal is formed on the first layer 120 and the exposed sidewall surface 110. In embodiments in which the first layer 120 is formed on the sidewall surface 110, as in the illustrated embodiment, the second layer 124 is formed closer to the central axis 116 than the first layer 120, but does not close the via hole 108. Step 206 is performed after the heat treatment step 204. Compared to the second metal, the first metal has a greater tendency to form an oxide that is covalently bonded to the desired surface of the glass substrate 100, such as the sidewall surface 110 of the via hole 108. The enthalpy of formation of such oxides is a kind of quantification of the above trend. In each embodiment, the absolute value of the enthalpy of formation of the oxide of the first metal is greater than the absolute value of the enthalpy of formation of the oxide of the second metal. In each embodiment, the absolute value of the enthalpy of formation of the oxide of the first metal is greater than 600 kJ per mole, but the absolute value of the enthalpy of formation of the oxide of the second metal is less than 600 kJ per mole. In each embodiment, the absolute value of the enthalpy of formation of the oxide of the first metal is greater than 325 kJ per mole, but the absolute value of the enthalpy of formation of the oxide of the second metal is less than 175 kJ per mole. In each embodiment, the absolute value of the enthalpy of formation of the oxide of the first metal is greater than 900 kJ per mole, but the absolute value of the enthalpy of formation of the oxide of the second metal is less than 175 kJ per mole. In various embodiments, the first metal of the second layer 124 includes one or more of tantalum, niobium, aluminum, manganese, rhenium, hafnium, chromium, zirconium, titanium, indium, tungsten, magnesium, molybdenum, nickel, and zinc, and the second metal of the second layer 124 includes one or more of silver, palladium, and copper. In various embodiments, the first metal of the second layer 124 is manganese or zinc, and the second metal of the second layer 124 is copper. Table 1 below lists the enthalpies of formation for various oxides of various metals.
[0075] [Table 1]
[0076] In each embodiment, forming 206 the second layer 124 of an alloy of the first metal and the second metal on the first layer 120 includes electrolessly plating the second layer 124 on the first layer 120 using a solution that contains (i) a salt of the first metal dissolved in the solution and (ii) a salt of the second metal dissolved in the solution. In electroless plating, ionic compounds of anions and cations of the first metal and anions and cations of the second metal are reduced by a chemical reducing agent to elemental forms of the first and second metals. A typical electroless plating process involves (a) a plating solution of ionic compounds containing cations of the first metal and cations of the second metal, (b) a reducing agent, (c) a pH adjuster, (d) a complexing agent to solubilize the ionic compounds, and (e) special additives to control the stability of the solution and the plating rate. These solutions are deposited on the glass component on which the first layer 120 of catalytic metal provides catalytically active surfaces. The catalytically active surface catalyzes the reduction of each metal cation of the ionic compound, resulting in the simultaneous deposition of the first and second metals in elemental form on the first layer 120 of the glass component (e.g., in the via hole 108), thus forming an alloy of the first and second metals as a second layer 124. Because the second layer 124 is autocatalytic, it further catalyzes additional first and second metals in elemental form to deposit on the second layer 124, thus increasing the thickness of the layer.
[0077] As discussed above, electroless plating processes incorporate and utilize a plating solution that includes an ionic compound of a first metal and an ionic compound of a second metal dissolved in a solvent. Suitable ionic compounds include, for example, the nitrates, sulfates, chlorides, acetates, and cyanides of the first and second metals, respectively. In one example of a plating solution, the ionic compound of the first metal is manganese sulfate monohydrate and the ionic compound of the second metal is copper sulfate pentahydrate. In another example of a plating solution, the ionic compound of the first metal is zinc chloride and the ionic compound of the second metal is copper sulfate pentahydrate. Typically, these ionic compounds are present at concentrations of about 0.001 mM (0.001 mol / m 3 ) to about 25 mM (25 mol / m 3 ) in solution. In embodiments, the ratio of the concentration of the ionic compound of the first metal to the concentration of the ionic compound of the second metal is in the range of 1:20000 to 1:1, such as in the range of 1:20 to 1:3, including about 1:4 or exactly 1:4. The solvent may be aqueous or any organic liquid suitable for the ionic compounds. Such organic liquids include, for example, alcohols, ethers, ketones, alkanes, and the like.
[0078] As described above, the electroless plating process incorporates and utilizes a reducing agent, a pH adjuster, and a complexing agent. The reducing agent reduces the metal cations present on the first layer 120 of the glass substrate 100. Specific examples of reducing agents include NaBH4, KBH4, NaH2PO2, hydrazine, formalin, formaldehyde, dimethylamine borane (DMAB), and polysaccharides (e.g., glucose). The pH adjuster adjusts the pH of the plating solution and may be an acidic or basic compound. In embodiments using formaldehyde as the reducing agent, a pH adjuster may be utilized to adjust the pH of the solution to 11 or greater. In embodiments using dimethylamine borane as the reducing agent, a pH adjuster may be utilized to adjust the pH of the solution to be approximately neutral (pH of about 7, e.g., pH 6 to pH 8).
[0079] The complexing agent prevents hydroxide precipitation in the alkaline solution and helps to prevent decomposition of ionic compounds and regulate the plating rate by controlling the concentrations of the first metal cation and the second metal cation. Specific examples of complexing agents include ammoniacal solution, acetic acid, guanic acid, tartaric acid, various chelating agents (e.g., ethylenediaminetetraacetic acid (EDTA)), Rochelle salt (potassium sodium tartrate tetrahydrate), various organic amine compounds, and the like.
[0080] In various embodiments, the temperature of the plating solution is in the range of 30° C. to 70° C., for example, about 60° C. In various embodiments, the glass substrate 100 is subjected to the electroless plating process for a time period in the range of 20 seconds to 30 minutes, for example, about 20 minutes. In various embodiments, the second layer of metal 124 resulting from the electroless plating has a thickness, designated 126, in the range of 10 nm to 100 nm, for example, about 50 nm. The second layer of metal 124 should be thick enough to ensure sufficient conductivity to allow for the subsequent application of a third layer of metal, as described below.
[0081] Heat treating the glass substrate 100 with the second layer 124: In step 208, the method 200 further includes exposing the glass substrate 100 with the second layer 124 of the alloy of the first metal and the second metal on the first layer 120 of the catalytic metal to a temperature between 250° C. and 600° C. for at least 30 minutes. In various embodiments, the temperature is between 300° C. and 450° C., such as between 375° C. and 425° C., for example, at or about 400° C. The heat treatment results in the formation of a glass component 128 (see FIG. 6 ), which comprises (i) the glass substrate 100, (ii) a first metal oxide 130 covalently bonded to the glass substrate 100, and (iii) a metal region 132 bonded to the first metal oxide 130. In various embodiments, the first metal oxide 130 excludes the second metal. Metal region 132 includes the catalytic metal in elemental form, the first metal in elemental form, and the second metal in elemental form. During the duration of the heat treatment of step 208, the first metal from second layer 124 displaces from first layer 120 of catalytic metal to form oxide 130 that bonds to the surface of glass substrate 100.
[0082] In various embodiments, the temperature of the environment surrounding the glass substrate 100 during step 208 is increased at a rate of 5° C. per minute or slower, such as 1° C. per minute or slower.
[0083] In various embodiments, the thermal treatment step 208 is performed with the glass substrate 100 in the presence of air. The presence of air can aid in the formation of an oxide 130 of the first metal bonded to the sidewall surface 110 of the glass substrate 100. In such embodiments, the method 200 further includes a thermal reduction step 210 in which the glass component 128 resulting from step 208 is exposed to a temperature of 225° C. to 275° C. in the presence of forming gas (a mixture of H2 and N2) for at least 30 minutes (e.g., 30 minutes to 90 minutes). The reduction step 210 restores the electrical conductivity of the metal regions 132 so that a third layer of metal can be subsequently applied over the metal regions 132, as described below.
[0084] Forming a third layer 134 of a primary metal on the glass component 128: At step 212, the method 200 further includes forming a third layer 134 of a primary metal on the metal region 132 of the glass component 128 (see FIG. 7). The primary metal is "primary" in the sense that it is the predominant metal in thickness on the glass component 128, i.e., the thickness 136 of the third layer 134 is greater than the thickness 122 of the first layer 120 and the thickness 126 of the second layer 124, respectively. If the glass component 128 is an interposer, the primary metal is the metal intended to perform the conductive function of the via hole 108, and also becomes the predominant metal within the via hole 108 after metallization according to the method 200. In various embodiments, the primary metal is or includes copper. In embodiments, the primary metal is or contains one or more of silver, gold, cadmium, chromium, copper, nickel, lead, platinum, and tin, and in embodiments, the thickness 136 of the third layer 134 of the primary metal is 2 μm or greater, for example, between 2 μm and 5 μm.
[0085] In each embodiment, forming the third layer 134 of the primary metal on the metal area 132 of the glass component 128 includes electroplating to produce the third layer 134 of the primary metal on the metal area 132 of the glass component 128. In the electroplating process, the glass component 128 is placed in a plating solution that includes an ionic compound having an anion and a cation of the primary metal that will form the third layer 134, and an electric current is applied. As a result, the elemental form of the primary metal is applied as the third layer 134 over the metal area 132 of the glass component 128. Anions of the ionic compound that includes the cation of the primary metal to be deposited include sulfate, nitrate, chloride, and the like. An example of an ionic compound used in a plating solution is copper sulfate. An example of a plating solution includes copper(II) sulfate pentahydrate (CuSO4·5H2O), potassium pyrophosphate (K4P2O7), and citric acid in distilled water. Another example of a plating solution contains copper(II) sulfate pentahydrate (CuSO4·5H2O), manganese(II) sulfate monohydrate (MnSO4·H2O), potassium sodium tartrate tetrahydrate (Rochelle salt), and formaldehyde. In each embodiment, the concentration of the ionic compounds in the plating solution is 0.001M (1 mol / m 3 ) or greater. The ionic compounds are dissolved in a liquid medium, such as deionized water. In addition to the glass component 128, electrodes made of any conductive material are also disposed in the plating solution. In various embodiments, the plating solution has a temperature between 10° C. and 50° C., for example, at room temperature or 40° C.
[0086] A current, a voltage, or a combination of both is applied between the electrodes and the glass component 128 to provide a constant negative current through the glass component 128. In various embodiments, the current density is in the range of about 0.001 mA / cm. 2 or about 1A / cm 2A voltage ranging from about -0.001V to about -20V is applied. As a result, the cations of the primary metal that will become the third layer 134 are reduced to elemental form over the entire surface of the metal area 132 of the glass component 128. The current density controls the rate of this reduction reaction. Thus, the deposition rate can be increased or decreased by increasing or decreasing the applied current. However, it should be noted that an applied current that is too high can result in a porous but void-filled deposit, and an applied current that is too low can prolong the process to the point that it becomes useless. After the third layer 134 of the primary metal is applied to the glass component 128 and covers the metal area 132, the current is stopped, the glass component 128 is removed from the plating solution, and the glass component 128 can be rinsed with deionized water. At this point, the glass component 128 can be optionally dried, such as by blowing a stream of nitrogen over the glass component 128.
[0087] In embodiments where the glass component 128 is intended to be an interposer, a third layer of primary metal 134 fills the remaining void of the via hole 108. Once the third layer of primary metal 134 has been applied by electroplating, the glass component 128 is placed in a plating solution to completely fill one or more of the via holes 108. The third layer of primary metal 134 is deposited on the metal area 132 of the glass component 128, and continues to build up until the via hole 108 is sealed and therefore fully metallized. In embodiments where the via hole 108 has an hourglass shape, the narrow neck 114 provides a metal "bridge" for the initially deposited conductive third layer of primary metal 134. The third layer of primary metal 134 continues to be deposited on either side of this bridge until the via hole 108 is filled. The "bridge" prevents deposition of the third layer of the primary metal 134 adjacent to the first side 102 or the second side 104, thereby helping to prevent the opening leading to the interior of the via hole 108 from closing before the via hole 108 is filled with the third layer of the primary metal 134. Otherwise, closing the opening leading to the interior of the via hole 108 would result in a void in the via hole 108, reducing electrical conductivity. When the via hole 108 is filled and completely metallized with the metal area 132 and the third layer of the primary metal 134, the via hole 108 allows electrical connection of electrical wiring of electrical components located directly or adjacent to the first side 102 and the second side 104 of the glass component 128. Once the third layer of the primary metal 134 fills the via hole 108 in the glass component 128, the current is stopped, isolating the plating solution from the glass component 128.
[0088] Heat treating the glass component 128 with the third layer 134 of the primary metal: In step 214, the method 200 further includes exposing the glass component 128 with the third layer 134 of the primary metal to a temperature of 250° C. to 600° C., for example, 300° C. to 400° C., more specifically, 325° C. to 375° C., or even about or at 350° C., for at least 30 minutes in an inert environment (such as a vacuum environment, a nitrogen environment, a forming gas environment, etc.). The heat treating step 214 forms a glass component 128 that includes (i) the glass substrate 100, (ii) the oxide 130 of the first metal covalently bonded to the glass substrate 100, and (iii) a new metal region 132 that contains the catalytic metal, the first metal, the second metal, and the primary metal all in elemental form (see FIG. 8). In other words, the heat treatment step 214 transforms the metal region 132 created in step 208 into a new metal region 138 that further contains the primary metal in elemental form.
[0089] One purpose of step 214 is to intermix the metal region 132 from step 208 with the third layer 134 of the primary metal added in step 212. Although temperatures below 325°C may serve that purpose, such temperatures may require an unduly long time to be practically useful. In other words, temperatures below 325°C for the duration of step 214 may result in the intermixing effect described above, but tend to take too long to be commercially practical. Temperatures of 375°C or less in step 214 are applicable to most glass substrates 100. Another purpose of step 214 is to relieve stresses that may have been generated in the glass component 128. For example, the laser machining process employed to form via holes 108 in a glass substrate 100 intended to be used as an interposer may cause thermal stresses within the glass substrate 100. The annealing step of the subsequent glass component 128 formed after the metallization step of the via hole 108 relieves any residual stresses that may be present in the glass substrate 100 .
[0090] In embodiments in which the glass component 128 is an interposer, the via hole 108 is now fully metallized, with the first metal covalently bonded to its sidewall surface 110 and the new metal region 138 covalently bonded to the oxide of the first metal. The oxide of the first metal 130 is thus disposed between the sidewall surface 110 of the through via hole 108 and the new metal region 138. The new metal region 138 forms a conductive path through the through via hole 108. The new metal region 138 is disposed within the through via hole 108 about the central axis 116. The new metal region 138 includes the first metal in elemental form, which is bonded to the oxide of the first metal 130. In each embodiment, portions of the first side 102 and second side 104 of the glass substrate 100 are metallized with a first metal oxide 130 covalently bonded to the first side 102 and second side 104 and new metal regions 138 containing the catalytic metal, the first metal, the second metal, and the primary metal, all in elemental form, bonded to the first metal oxide 130. The new metal regions 138 are expected to be primarily the primary metal at and near the central axis 116.
[0091] The formation and incorporation of the first metal oxide 130 allows the primary metal (e.g., copper) to adhere more effectively to the glass substrate 100. The second layer 124 of the alloy of the first and second metals thus functions to (i) promote adhesion of the subsequently applied metal to the glass substrate 100 by forming the first metal oxide 130, and (ii) promote application of the third layer 134 of the primary metal, since the second metal of the second layer 124 of the alloy is unlikely to form an oxide and the metal region 132 resulting from step 208 is assured to be sufficiently conductive to contribute to the formation of the third layer 134 of the primary metal in step 212 (e.g., by electroplating). The combination of the first metal oxide 130 covalently bonded to the sidewall surface 110 of the glass substrate 100 and the metallic bonding and intermixing of the catalytic metal, the first metal, the second metal, and the primary metal in the new metal region 138 results in strong adhesion of the primary metal to the glass substrate 100. Additionally, all of steps 202, 206, and 212 of forming first layer 120, second layer 124, and third layer 134 are solution-based, which allows via hole 108 to be fully metallized in a cost-effective manner without significant voids (e.g., pinholes), even for high aspect ratio via holes. EXAMPLES
[0092] Example 1. According to step 202 of method 200, a first layer 120 of silver as a catalytic metal was formed on a first side 102 of a sample glass substrate 100. The glass substrate 100 for this example and all further examples below was an alkaline earth aluminoborosilicate glass substrate. More specifically, silver nanoparticles were dispersed in a liquid carrier. The nanoparticles had an average size of 10 nm to 13 nm. The liquid carrier was cyclohexane. The concentration of the silver nanoparticles was 20% w / v of cyclohexane. The dispersion was subjected to ultrasonic treatment for 30 minutes to help separate the agglomerates of silver nanoparticles. The dispersion was then spun onto the first side 102 of the glass substrate 100 at a spin speed of 1000 RPM. The liquid carrier was allowed to evaporate. Next, in accordance with step 204 of method 200, the sample of glass substrate 100 having the first layer of catalytic metal (silver) 120 thereon was exposed to 350°C for 2 minutes in an air environment, thus forming a glass substrate 100 having the catalytic metal disposed as a first layer on the first surface 102.
[0093] Next, according to step 206 of method 200, a second layer 124 of alloy was formed on the catalytic metal by electroless deposition. The bath solution used for electroless deposition had the composition set forth in Table 2 below, and the ratio of the concentration of the ionic compound of manganese as the first metal to the concentration of the ionic compound of copper as the second metal was 1:4.
[0094] [Table 2]
[0095] The pH of the electroless plating bath was adjusted to 12.5. The temperature of the electroless plating bath was maintained at 60° C. The glass substrate 100 having the silver catalytic metal was immersed in the bath for 20 minutes. The glass substrate 100 was then removed from the bath, rinsed with water, and dried in a nitrogen environment. Thus, the resulting second layer 124 was an alloy of manganese as the first metal and copper as the second metal.
[0096] Next, in accordance with step 208 of method 200, the glass substrate 100 with the second layer of alloy 124 was exposed to a temperature of 400° C. for 30 minutes in an air environment. The temperature was ramped up to 400° C. at a rate of 1° C. per minute. X-ray photoelectron spectroscopy (XPS) was utilized to determine the elemental composition of the resulting glass part 128 with the metal region 132. The results are shown in Table 3 below.
[0097] [Table 3]
[0098] This result demonstrates that steps 202 through 208 did indeed result in metal regions 132 containing manganese and copper from the electroless plating bath, and silver from spin-on. The presence of carbon likely originates from the electroless plating bath, or may be atmospheric.
[0099] Next, in accordance with step 212 of method 200, a third layer 134 of primary metal (copper) was applied over metal area 132 by an electroplating process. The electroplating process utilized a non-acidic plating solution of copper sulfate dissolved in deionized water. A copper plate was used as the anode. A constant current of 50 mA was applied for 1 hour, resulting in a third layer 134 of copper having a thickness 134 of 2.5 μm. The glass part 128 was then removed from the plating solution and rinsed.
[0100] Next, in accordance with step 214 of method 200, the glass component 128 having the third layer 134 of primary metal (copper) thereon was exposed to a temperature of 350° C. for 30 minutes under vacuum, with a controlled ramp rate of 5° C. per minute to reach 350° C.
[0101] 9, the resulting glass part 128 was tested for adhesion of the new metal area 138 to the glass substrate 100 by performing a cross-hatch tape test according to ASTM D3359-09 (Standard Test Method for Measuring Adhesion by Tape Test). For the tape test, a checkerboard pattern with 11 cuts per direction was made deep into the new metal area 138. A pressure sensitive tape 140 was then applied over the checkerboard pattern. The tape 140 was then removed. The amount and type of removal was then compared to the descriptions and illustrations in the ASTM document. The removal of the tape 140 removed less than 5% of the new metal area 138 from the glass part 128. According to the ASTM standard, the test result was 4B or 5B, indicating a high level of adhesion of the new metal area 138 containing copper, manganese, and silver to the glass substrate 100.
[0102] Example 2. According to steps 202 and 204 of the method 200, a first layer 120 of silver as a catalytic metal was formed on the first surface 102 of a sample glass substrate 100 in the same manner as in Example 1, and then subjected to a heat treatment.
[0103] A second layer 124 of alloy was then formed on the catalytic metal by electroless deposition in accordance with step 206 of method 200. The bath solution used for electroless deposition had the composition as set forth in Table 4 below.
[0104] [Table 4]
[0105] The pH of the electroless plating bath was adjusted to 12.5. The temperature of the electroless plating bath was maintained at 60° C. The glass substrate 100 with the silver catalytic metal was immersed in the bath for 20 minutes. The glass substrate 100 was then removed from the bath, rinsed with water, and dried in a nitrogen environment. Thus, the resulting second layer 124 was an alloy of zinc as the first metal and copper as the second metal.
[0106] Next, in accordance with step 208 of method 200, the glass substrate 100 with the alloy second layer 124 disposed thereon was exposed to a temperature of 400° C. for 30 minutes in an air environment. The temperature was ramped up to 400° C. at a rate of 1° C. per minute. X-ray photoelectron spectroscopy (XPS) was utilized to determine the elemental composition of the metal region 132 after the heat treatment step 208. The results are shown in Table 5 below.
[0107] [Table 5]
[0108] This result demonstrates that steps 202 through 208 result in a metal region 132 containing zinc and copper from the electroless plating bath and silver from the spin-on process.
[0109] Next, following steps 212 and 214 of method 200, a third layer 134 of primary metal (copper) was applied over metal region 132 by an electroplating process and then subjected to a heat treatment in the same manner as in Example 1.
[0110] 10, the resulting glass part 128 was subjected to a cross-hatch tape test in accordance with ASTM D3359-09 to test the adhesion of the resulting new metal area 138 to the glass substrate 100. For the tape test, a checkerboard pattern with 11 cuts per direction was made deep into the new metal area 138. A pressure sensitive tape 140 was then applied over the checkerboard pattern. The tape 140 was then removed and the amount and type of removal was compared to the ASTM document description and illustration. The tape 140 removed less than 5% of the new metal area 138 from the glass part 128. According to the ASTM standard, the test result was 4B, indicating a high level of adhesion of the new metal area 138 containing copper, zinc, and silver to the glass substrate 100.
[0111] Example 3. Following steps 202 and 204 of method 200, a first layer 120 of palladium as a catalytic metal was formed on the first surface 102 of a sample glass substrate 100 in the same manner as in Example 1, and then subjected to a heat treatment.
[0112] Next, in accordance with step 206 of method 200, a second layer 124 of alloy was formed on the first layer 120 of catalytic metal by electroless deposition. The composition of the electroless plating bath is shown in Table 6 below.
[0113] [Table 6]
[0114] The temperature of the electroless plating bath was maintained at 43° C. Thus, the second layer 124 is an alloy of manganese as the first metal and copper as the second metal. In accordance with step 208 of method 200, the glass substrate 100 provided with the second layer 124 of manganese and copper alloy was exposed to 400° C. for 30 minutes in an air environment after a controlled temperature ramp of 1° C. per minute. The resulting glass part 128 was then exposed to a temperature of 250° C. for 30 minutes in forming gas, thereby reducing any copper oxide resulting from step 208 which occurred in an air environment, in accordance with step 210 of method 200.
[0115] Next, in accordance with step 212 of method 200, a third layer 134 of the primary metal (copper) was applied over metal region 132 by an electroplating process. Third layer 134 had a thickness 136 of 2.5 μm.
[0116] Next, in accordance with step 214 of method 200, glass component 128 having primary metal third layer 134 (copper) thereon was subjected to a temperature of 350° C. under vacuum for 30 minutes.
[0117] 11, the resulting glass part 128 was subjected to a cross-hatch tape test in accordance with ASTM D3359-09 to test the adhesion of the new metal area 138 to the glass substrate 100. For this tape test, a grid pattern with 11 cuts per direction was made deep into the new metal area 138. A pressure sensitive tape 140 was then applied over the grid pattern. The tape 140 was then removed. The amount and type of removal was then compared to the description and illustration in the ASTM document. The removal of the tape 140 removed less than 5% of the new metal area 138 from the glass part 128. According to the ASTM standard, the test result was 4B. This indicates a high level of adhesion of the new metal area 138 containing copper, manganese, and silver to the glass substrate 100, even though the electroless plating bath had a lower concentration of manganese compared to the electroless plating bath of Example 1.
[0118] Comparative Example 1. In Comparative Example 1, a glass substrate 100 having a catalytic metal film was prepared by applying a first layer 120 of catalytic metal (silver) to a first surface 102 of the glass substrate 100 and then exposing it to high temperature. A second layer 124 of an alloy of the first metal (which tends to form an oxide 130) and a second metal was not deposited on the first layer 120. Instead, a 2.5 μm thick layer of copper was electroplated onto the first layer 120 of catalytic metal and then exposed to high temperature under reduced pressure for a period of time.
[0119] Referring now to FIG. 12, a cross-hatch tape test was performed in accordance with ASTM D3359-09 to test the adhesion of electroplated copper and silver to a glass substrate 100. For the tape test, a grid pattern with 11 cuts per direction was made deep into the metal layer. A pressure sensitive tape 140 was then applied over the grid pattern. The tape 140 was then removed. The amount and type of removal was then compared to the descriptions and illustrations in the ASTM document. The removal of the tape 140 removed essentially all of the electroplated copper and spin-on silver from the glass substrate 100. According to the ASTM standard, the test result was 0B, which indicates a very low level of adhesion of the electroplated copper and spin-on silver to the glass substrate 100. This illustrates that each step of the method 200 for applying an alloy including a first metal that forms an oxide 130 that bonds with the first side 102 of the glass substrate 100 is important to bond the primary metal to the first side 102 of the glass substrate 100.
[0120] Comparative Example 2. In Comparative Example 2, a first layer 120 of catalytic metal (silver) was applied to the first surface 102 of a glass substrate 100 and then exposed to high temperatures. Then, instead of electrolessly depositing a second layer 124 of an alloy of the first metal (which is more likely to form oxides 130) and the second metal onto the catalytic metal, only copper (which is less likely to form oxides 130) was electrolessly deposited onto the first layer 120. The glass substrate 100 with the first layer 120 of silver and the electrolessly deposited copper layer was then exposed to 400° C. for 30 minutes after reaching said temperature at a controlled ramp rate of 1° C. per minute in an air environment. The sample was then exposed to 250° C. for 30 minutes in a forming gas environment. A 2.5 μm thick layer of copper was electroplated over the electrolessly deposited copper layer. The sample was then exposed to 350° C. for 30 minutes under reduced pressure.
[0121] Referring now to FIG. 13, the resulting glass parts were subjected to a cross-hatch tape test in accordance with ASTM D3359-09 to test the adhesion of electroplated copper, electrolessly deposited copper, and spin-on silver to the glass substrate 100. For the tape test, a checkerboard pattern with 11 cuts per direction was made deep into the new metal area. Pressure sensitive tape 140 was then applied over the checkerboard pattern. The tape 140 was then removed. The amount and type of removal was then compared to the ASTM document description and illustration. The removal of the tape 140 removed nearly 100% of the deposited metal from the glass substrate 100. Per ASTM standards, the test result was 0B, indicating very poor adhesion of each deposited metal to the glass substrate 100. This illustrates that step 206 of method 200 for applying an alloy containing a first metal forming an oxide 130 bonded to the first side 102 of the glass substrate 100 is important for bonding the primary metal (e.g., copper) as well as each of the other metals to the first side 102 of the glass substrate 100.
[0122] It will be apparent to those skilled in the art that various modifications and variations can be made without departing from the spirit or scope of the claims.
[0123] Preferred embodiments of the present invention will be described below in detail.
[0124] EMBODIMENT 1 1. A method for producing a glass part, comprising: forming a first layer of catalytic metal on a surface of a glass substrate; exposing the glass substrate having the first layer of catalytic metal thereon to a temperature of between 150° C. and 600° C. for at least 2 minutes; forming a second layer of an alloy of the first metal and the second metal on the first layer; forming a glass component by exposing a glass substrate having a first layer of catalytic metal thereon and a second layer of an alloy of a first metal and a second metal to a temperature of 250° C. to 600° C. for at least 30 minutes, the glass component comprising: (i) the glass substrate; (ii) an oxide of the first metal covalently bonded to the glass substrate; and (iii) a metal region bonded to the oxide of the first metal, the metal region including the catalytic metal in elemental form, the first metal in elemental form, and the second metal in elemental form; The method includes:
[0125] EMBODIMENT 2 2. The method of embodiment 1, further comprising forming a third layer of a primary metal over the metal region of the glass component.
[0126] EMBODIMENT 3 3. The method of embodiment 2, further comprising exposing the glass component having the third layer of the primary metal to a temperature of 250° C. to 600° C. in an inert environment for at least 30 minutes to form a glass component comprised of: (i) a glass substrate; (ii) an oxide of the first metal covalently bonded to the glass substrate; and (iii) a new metal region comprising the catalytic metal, the first metal in elemental form, the second metal in elemental form, and the primary metal in elemental form.
[0127] EMBODIMENT 4 The method of any one of embodiments 1 to 3, wherein the catalytic metal comprises one or more of silver, gold, cobalt, a cobalt-phosphorus alloy, nickel or a nickel-phosphorus alloy, palladium, and platinum.
[0128] EMBODIMENT 5 The step of forming a first layer of catalytic metal on the surface includes contacting the surface with a suspension in which nanoparticles of the catalytic metal are dispersed in a liquid support; and vaporizing the liquid phase carrier.
[0129] EMBODIMENT 6 6. The method of embodiment 5, wherein the step of contacting the surface with the suspension comprises spinning the suspension onto the surface.
[0130] EMBODIMENT 7 The method of any one of embodiments 1 to 6, wherein the glass substrate has a first surface and a second surface as its two main surfaces, and sidewall surfaces defining a through via hole opening at the first surface and the second surface and extending through the glass substrate, and an oxide of the first metal is covalently bonded to the sidewall surfaces of the through via hole.
[0131] EMBODIMENT 8 The glass substrate has a first surface and a second surface as its two main surfaces, and sidewall surfaces that open at the first surface and the second surface and define a through via hole that extends through the glass substrate; an oxide of the first metal is covalently bonded to a sidewall surface of the through via hole; 4. The method of embodiment 3, wherein the new metal area forms a conductive path through the through via hole.
[0132] EMBODIMENT 9 The glass substrate has a first surface and a second surface as its two main surfaces, and a sidewall surface defining a blind via hole that opens in one of the first surface and the second surface and extends insufficiently through the glass substrate; The method of any one of embodiments 1 to 6, wherein an oxide of the first metal is covalently bonded to a sidewall surface of the blind via hole.
[0133] EMBODIMENT 10 the first metal of the second layer includes one or more of tantalum, niobium, aluminum, manganese, rhenium, hafnium, chromium, zirconium, titanium, indium, tungsten, magnesium, molybdenum, nickel, and zinc; The method of any one of embodiments 1 through 9, wherein the second metal of the second layer comprises one or more of silver, palladium, and copper.
[0134] EMBODIMENT 11 The method of any one of embodiments 1 through 10, wherein the oxide of the first metal excludes the second metal.
[0135] EMBODIMENT 12 The method of any one of embodiments 1 through 11, wherein the second metal of the second layer is copper.
[0136] EMBODIMENT 13 The method of any one of embodiments 1 through 12, wherein the first metal of the second layer is manganese or zinc.
[0137] EMBODIMENT 14 The oxide of the first metal of the alloy has an enthalpy of formation greater than 600 kJ per mole; The method of any one of the preceding embodiments, wherein the oxide of the second metal of the alloy has an absolute enthalpy of formation of less than 600 kJ per mole.
[0138] EMBODIMENT 15 15. The method of any one of embodiments 1 to 14, wherein forming the second layer of alloy comprises producing the second layer on the first layer by electroless plating using a solution having a salt of the first metal dissolved therein and a salt of the second metal dissolved therein.
[0139] EMBODIMENT 16 16. The method of embodiment 15, wherein the solution further comprises formaldehyde and has a pH greater than 11.
[0140] EMBODIMENT 17 The method of embodiment 15, wherein the solution further comprises dimethylamine borane and has a pH of 6 to 8.
[0141] EMBODIMENT 18 18. The method of any one of claims 1 to 17, wherein exposing the glass substrate having the first layer of catalytic metal thereon and the second layer of an alloy of the first metal and the second metal to a temperature of 250°C to 600°C includes increasing the temperature at a rate of 1°C per minute or slower.
[0142] EMBODIMENT 19 The step of exposing the glass substrate having the second layer of the alloy of the first metal and the second metal formed on the first layer of the catalytic metal to a temperature of 250° C. to 600° C. is carried out in a state where the glass substrate is in the presence of air; 19. The method of any one of the preceding claims, wherein the method further comprises exposing the glass component to a temperature of 225°C to 275°C for at least 30 minutes while the glass component is in the presence of forming gas after exposing the glass component to a temperature of 375°C to 425°C.
[0143] EMBODIMENT 20 The method of embodiment 2, wherein the primary metal comprises one or more of silver, gold, cadmium, chromium, copper, nickel, lead, platinum, and tin.
[0144] EMBODIMENT 21 3. The method of embodiment 2, wherein the primary metal comprises copper.
[0145] EMBODIMENT 22 The method of any one of embodiments 2, 20, and 21, wherein the third layer is 2 μm to 5 μm thick.
[0146] EMBODIMENT 23 The method of any one of embodiments 20 to 22, wherein forming a third layer of a primary metal on the metal region of the glass component includes producing a third layer of a primary metal on the metal region of the glass component by electroplating.
[0147] EMBODIMENT 24 24. The method of embodiment 23, wherein the electroplating step utilizes a plating solution comprising copper sulfate.
[0148] EMBODIMENT 25 the step of exposing the glass substrate having the first layer of catalytic metal thereon to a temperature of 150° C. to 600° C. for at least 2 minutes includes exposing the glass substrate having the first layer of catalytic metal thereon to a temperature of 325° C. to 375° C. for at least 2 minutes; 25. The method of any one of claims 1 to 24, wherein the step of exposing the glass substrate having the second layer of an alloy of the first metal and the second metal disposed on the first layer of catalytic metal to a temperature of 250°C to 600°C for at least 30 minutes comprises exposing the glass substrate having the second layer of an alloy of the first metal and the second metal disposed on the first layer of catalytic metal to a temperature of 300°C to 425°C for at least 30 minutes.
[0149] EMBODIMENT 26 the step of exposing the glass substrate having the first layer of catalytic metal thereon to a temperature of 150° C. to 600° C. for at least 2 minutes includes exposing the glass substrate having the first layer of catalytic metal thereon to a temperature of 325° C. to 375° C. for at least 2 minutes; the step of exposing the glass substrate having the second layer of an alloy of the first metal and the second metal disposed on the first layer of catalytic metal to a temperature of 250° C. to 600° C. for at least 30 minutes includes exposing the glass substrate having the second layer of an alloy of the first metal and the second metal disposed on the first layer of catalytic metal to a temperature of 300° C. to 425° C. for at least 30 minutes; The method of embodiment 3, wherein the step of exposing the glass component having the third layer of the primary metal disposed thereon to a temperature of between 250° C. and 600° C. in an inert environment for at least 30 minutes comprises exposing the glass component having the third layer of the primary metal disposed thereon to a temperature of between 300° C. and 400° C. in an inert environment for at least 30 minutes.
[0150] EMBODIMENT 27 The method of embodiment 3 or embodiment 26, wherein the inert environment is a reduced pressure environment.
[0151] EMBODIMENT 28 In glass interposers, A glass substrate having a first surface and a second surface as front and back main surfaces, and a through via hole extending through a thickness from the first surface to the second surface, the through via hole having a side wall surface and a central axis; a metal region disposed about a central axis of the through via hole; an oxide of a first metal covalently bonded to a sidewall surface of the through via hole; It is equipped with A glass interposer, wherein an oxide of a first metal is disposed between the sidewall surface and a metal region, the metal region including the first metal in elemental form and a second metal in elemental form.
[0152] EMBODIMENT 29 the first metal is one or more of tantalum, niobium, aluminum, manganese, rhenium, hafnium, chromium, zirconium, titanium, indium, tungsten, magnesium, molybdenum, nickel, and zinc; 29. The glass interposer of embodiment 28, wherein the second metal is one or more of silver, palladium, and copper.
[0153] EMBODIMENT 30 The oxide of the first metal has an absolute enthalpy of formation greater than 325 kJ per mole; 29. The glass interposer of embodiment 28, wherein the oxide of the second metal has an absolute enthalpy of formation less than 175 kJ per mole.
[0154] EMBODIMENT 31 29. The glass interposer of embodiment 28, wherein the first metal is manganese and the second metal is copper.
[0155] EMBODIMENT 32 The glass interposer of any one of embodiments 28 to 31, wherein the metal region further comprises silver. [Explanation of symbols]
[0156] 100 Glass substrate 102 Page 1 104 2nd page 108 Via Hole 110 Side wall 120 1st layer 124 2nd layer 128 Glass parts 130 Oxides 132 Metal area 134 3rd layer 138 Metal area
Claims
1. 1. A method for producing a glass part, comprising: forming a first layer of catalytic metal on a surface of a glass substrate; exposing the glass substrate having the first layer of catalytic metal thereon to a temperature of 150° C. to 600° C. for at least 2 minutes; forming a second layer of an alloy of the first metal and a second metal on the first layer; forming a glass component by exposing a glass substrate having a first layer of catalytic metal thereon and a second layer of an alloy of a first metal and a second metal to a temperature of 250° C. to 600° C. for at least 30 minutes, the glass component comprising: (i) the glass substrate; (ii) an oxide of the first metal covalently bonded to the glass substrate; and (iii) a metal region bonded to the oxide of the first metal, the metal region including the catalytic metal in elemental form, the first metal in elemental form, and the second metal in elemental form; forming a third layer of a primary metal over the metal region of the glass component; and exposing the glass component having the third layer of the primary metal to a temperature of 250° C. to 600° C. in an inert environment for at least 30 minutes to form a glass component comprised of: (i) a glass substrate; (ii) an oxide of the first metal covalently bonded to the glass substrate; and (iii) a new metal region comprising a catalytic metal, the first metal in elemental form, the second metal in elemental form, and the primary metal in elemental form.
2. The glass substrate has a first surface and a second surface as its two main surfaces, and sidewall surfaces that open at the first surface and the second surface and define a through via hole that extends through the glass substrate; an oxide of the first metal is covalently bonded to a sidewall surface of the through via hole; The method of claim 1 , wherein the new metal area forms a conductive path through a through via hole.
3. the catalytic metal includes one or more of silver, gold, cobalt, cobalt-phosphorus alloy, nickel or nickel-phosphorus alloy, palladium, and platinum; the first metal of the second layer includes one or more of tantalum, niobium, aluminum, manganese, rhenium, hafnium, chromium, zirconium, titanium, indium, tungsten, magnesium, molybdenum, nickel, and zinc; the second metal of the second layer includes one or more of silver, palladium, and copper; The method of claim 1 or claim 2, wherein the primary metal comprises one or more of silver, gold, cadmium, chromium, copper, nickel, lead, platinum, and tin.
4. the oxide of the first metal of the alloy has an enthalpy of formation greater than 600 kJ per mole; 4. The method of claim 1, wherein the oxide of the second metal of the alloy has an absolute enthalpy of formation of less than 600 kJ per mole.
5. 5. The method of claim 1, wherein the step of forming the second layer of alloy includes producing the second layer on the first layer by electroless plating using a solution having a salt of the first metal dissolved therein and a salt of the second metal dissolved therein.
6. 6. The method of claim 1, wherein forming a third layer of the primary metal on the metal region of the glass component comprises producing a third layer of the primary metal on the metal region of the glass component by electroplating.
7. the step of exposing the glass substrate having the first layer of catalytic metal thereon to a temperature of 150° C. to 600° C. for at least 2 minutes comprises exposing the glass substrate having the first layer of catalytic metal thereon to a temperature of 325° C. to 375° C. for at least 2 minutes; the step of exposing the glass substrate having the second layer of an alloy of the first metal and the second metal disposed on the first layer of catalytic metal to a temperature of 250° C. to 600° C. for at least 30 minutes includes exposing the glass substrate having the second layer of an alloy of the first metal and the second metal disposed on the first layer of catalytic metal to a temperature of 300° C. to 425° C. for at least 30 minutes; 7. The method of claim 1, wherein the step of exposing the glass component provided with the third layer of the primary metal to a temperature of between 250°C and 600°C in an inert environment for at least 30 minutes comprises exposing the glass component provided with the third layer of the primary metal to a temperature of between 300°C and 400°C in an inert environment for at least 30 minutes.
8. In glass interposers, A glass substrate having a first surface and a second surface as front and back main surfaces, and a through via hole extending through a thickness from the first surface to the second surface, the through via hole having a side wall surface and a central axis; a metal region disposed about a central axis of the through via hole; an oxide of a first metal covalently bonded to a sidewall surface of the through via hole; It is equipped with A glass interposer, wherein an oxide of a first metal is disposed between the sidewall surface and the metal region, the metal region including the first metal in elemental form and a second metal in elemental form.
9. the first metal is one or more of tantalum, niobium, aluminum, manganese, rhenium, hafnium, chromium, zirconium, titanium, indium, tungsten, magnesium, molybdenum, nickel, and zinc; The glass interposer of claim 8 , wherein the second metal is one or more of silver, palladium, and copper.
10. The oxide of the first metal has an absolute enthalpy of formation greater than 325 kJ per mole; 9. The glass interposer of claim 8, wherein the oxide of the second metal has an absolute enthalpy of formation of less than 175 kJ per mole.
Citation Information
Patent Citations
A Novel Adhesion Promotion Method for Metallizing Substrate Surfaces
JP2016533429A
A Novel Adhesion Promoter for Metallizing Substrate Surfaces
JP2016533430A
Semiconductor device
JP2017092485A
Through-electrode substrate, method for manufacturing the same, and semiconductor device
JP2018125348A
Wiring board, semiconductor package, and manufacturing method of wiring board
JP2020009813A